Sequence dependence for bypass of thymine glycols in DNA by DNA polymerase I. - Hayes, R C (1986)
Single-stranded phage DNAs containing thymine glycols were prepared by oxidation with osmium tetroxide (OsO4) and were used as templates for DNA synthesis by E. coli DNA polymerase I. The induction of thymine glycol lesions in DNA, as measured by immunoassay, quantitatively accounted for an inhibition of in vitro DNA synthesis on modified templates. Analysis of termination sites for synthesis by DNA polymerase I (Klenow fragment) showed that DNA synthesis terminated at most template thymine sites in OsO4-treated DNA, indicating that incorporation occurred opposite putative thymine glycols in DNA. Nucleotides 5' and 3' to putative thymine glycol sites affect the reaction, however, since termination was not observed at thymines in the sequence 5'-CTPur-3'. Conversion of thymine glycols to urea residues in DNA by alkali treatment caused termination of DNA synthesis one nucleotide 3' to template thymine sites, including thymines in the 5'-CTPur-3' sequence, showing that the effect of surrounding sequence is on the elongation reaction by DNA polymerase rather than differential damage induction by OsO4.